Model Transformasi Informasi Artikel Minangkabau sebagai Preservasi Pengetahuan tentang Budaya Lokal - Nelisa, Malta; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2022)
Newspaper articles are intellectual works of individuals that need to be respected as a form of information which can provide valuable knowledge to the reading community about various aspects of life. This source of information is frequently used as a primary reference to support various community activities such as developing knowledge and general insight. So far, there is no system of information available for continuous documentation for articles containing Minangkabau in printed newspapers. The writing of this paper aimed to explain the transformation model of Minangkabau articles in printed newspapers become information that can be accessed digitally. The research method used was research and design. Determination of the sample was using purposive sampling technique with specific criteria. The conditions is sample contains information that can be used all the time and comprehensively discuss one aspect of the lives of Minangkabau community. The study was conducted on 127 articles containing Minangkabau found in four newspapers which is spread in West Sumatra particularly Singgalang, Padang Ekspres, Posmetro, and Haluan through the use of the concept of information transformation and preservation of knowledge. The results of the study showed that the information transformation model of Minangkabau articles begins with article selection, article documentation in the form of clipping, indexation, context diagram formation and User Interface configuration as a design for digital documentation.